Solvent-free epoxy anticorrosive paint and preparation method thereof
Through the synergistic effect of modified epoxy resin and nano zinc oxide, combined with silane coupling agent and dispersion process, the problems of uneven coating and difficult construction of solvent-free epoxy anti-corrosion coatings are solved, and a high-performance, low-VOC anti-corrosion coating with good construction performance and protective effect is achieved.
Patent Information
- Application Number
- CN202511258355.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-10-14
AI Technical Summary
Existing solvent-free epoxy anti-corrosion coatings have problems such as wide molecular weight distribution of the resin system, poor dispersion of pigments and fillers, and difficulty in viscosity control, which lead to uneven mechanical properties of the coating and great difficulty in construction. In addition, the traditional curing system is prone to bubbles or defects, affecting the anti-corrosion effect.
The resin structure is optimized through the synergistic effect of modified epoxy resin and modified nano-zinc oxide, combined with the modification of silane coupling agent and polyvinyl butyral; the modified nano-zinc oxide is coated with esterification and composite oxides to enhance the compatibility with the resin matrix; and the high-speed dispersion process and real-time feedback control of viscosity are used to ensure the uniformity and stability of the coating.
It achieves a dense continuous network structure of the coating, improves impact resistance and adhesion, reduces VOC content, ensures leveling and stability during construction, avoids bubbles and defects, and improves corrosion resistance and environmental protection.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of paint, in particular to a solvent-free epoxy anticorrosive paint and a preparation method thereof. BACKGROUND
[0002] In the field of paint technology, anticorrosive paint is an important protective means for metal materials and components, and is widely used in harsh environments such as petroleum chemical industry, ocean engineering, bridge construction, etc. Although traditional solvent-based epoxy anticorrosive paint has certain corrosion resistance, it contains a large amount of volatile organic compounds (VOCs), which not only causes resource waste, but also causes environmental pollution and harm to human health, etc., which is contrary to the current green and environmentally friendly development concept.
[0003] Solvent-free epoxy anticorrosive paint has become an important direction to replace traditional solvent-based paint due to its non-volatile solvent and extremely low VOC emission. However, there are many technical bottlenecks in the actual application of existing solvent-free epoxy paint: first, the wide molecular weight distribution of the resin system leads to uneven mechanical properties of the coating, and easy cracking, peeling and other phenomena; second, the poor dispersion of pigments and fillers easily causes agglomeration, reduces the compactness of the coating, and affects the corrosion protection effect; third, the viscosity of the system is difficult to control, and problems such as sagging or incomplete curing are easily occurred during the construction process, making it difficult to balance the workability and performance stability.
[0004] In addition, ordinary functional fillers such as nano zinc oxide have poor compatibility in paint, and cannot fully play their role in strengthening and corrosion protection; the reaction rate of the traditional curing system is not easy to control, which easily leads to the generation of bubbles or defects in the coating, further weakening the protective performance. These problems seriously restrict the performance improvement and application expansion of solvent-free epoxy anticorrosive paint, and it is urgent to develop a solvent-free epoxy anticorrosive paint with excellent environmental performance, high mechanical strength, good corrosion protection effect and stable workability, and a preparation method thereof. SUMMARY
[0005] In view of the deficiencies of the prior art, the present application provides a solvent-free epoxy anticorrosive paint and a preparation method thereof, which solves the problems of poor environmental performance, uneven performance and difficult construction of traditional paint.
[0006] To achieve the above purpose, the present application realizes the following technical scheme:
[0007] A solvent-free epoxy anticorrosive paint, comprising the following raw materials by weight: 40-60 parts of modified epoxy resin, 5-10 parts of modified nano zinc oxide, 15-25 parts of polyamide curing agent, 5-10 parts of butyl glycidyl ether, 10-15 parts of titanium dioxide, 8-12 parts of talc, 5-8 parts of barium sulfate, 0.5-1 part of silicone defoaming agent, 0.5-1 part of acrylate leveling agent, 1-2 parts of silane coupling agent KH-550, 3-5 parts of carboxyl-terminated butyl nitrile rubber, and 1-2 parts of fumed silica.
[0008] Further, the modified epoxy resin, the specific preparation steps are as follows:
[0009] A1, the epoxy resin E-51 is added to the reaction kettle, the temperature is raised to 80-90℃, the epoxy chloropropane, anhydrous aluminum chloride and ethyl acetate are slowly added under the stirring of 400-500r / min, after adding, the reaction is kept for 2-3h, during which the epoxy value is measured every 30min, when the epoxy value is stable at 0.35-0.4eq / 100g, the reaction is stopped, and the epoxy ring opening prepolymer is obtained;
[0010] Under the catalysis of Lewis acid anhydrous aluminum chloride, the epoxy group of epoxy resin E-51 undergoes ring opening reaction, chain transfer and addition with epoxy chloropropane, forming a linear prepolymer with active end groups. By real-time monitoring of epoxy value, the ring opening degree is accurately controlled to provide a structure uniform reaction intermediate for subsequent chain extension;
[0011] A2, the above prepolymer is added with bisphenol A, sodium hydroxide and phthalic anhydride, the temperature is raised to 110-120℃, the reaction is carried out for 3-4h, during which the generated water is separated by water trap, the viscosity is measured every hour, when the viscosity reaches 5000-6000mPa・s, the remaining alkalinity is neutralized by adding phosphoric acid, and the chain extension modified epoxy intermediate is obtained;
[0012] The ring opening prepolymer and bisphenol A undergo condensation chain extension reaction under alkaline conditions, and phthalic anhydride participates in chain segment control. Through the "water separation-viscosity real-time feedback" process, the water generated in the reaction is continuously separated to promote the forward reaction, and the viscosity is monitored to terminate the reaction, so that the molecular weight distribution width is controlled in 1.2-1.5, avoiding the performance uneven caused by excessive growth of molecular chain or too wide distribution;
[0013] A3, the above intermediate is cooled to 70-80℃, silane coupling agent KH-560, silane coupling agent KH-550 and polyvinyl butyral are added, and the stirring is carried out at 500-600r / min for 1-2h, during which nitrogen protection is carried out, after the reaction is completed, the temperature is lowered to room temperature, and the modified epoxy resin is obtained.
[0014] The silane coupling agent KH-560 is introduced, the epoxy group reacts with the resin hydroxyl group, the alkoxyl group forms a covalent bond with the surface of the pigment and filler after hydrolysis, the interface bonding between the resin and the filler is strengthened, the delamination is reduced, and the mechanical strength of the coating is improved; the amino group of silane coupling agent KH-550 reacts with the epoxy group of the resin, and the polar group enhances the adsorption force to the substrate, the adhesion between the coating and the substrate is improved, and the interface debonding is reduced; polyvinyl butyral modifies the resin main chain by chain winding, enhances the flexibility of the molecular chain, and improves the impact resistance of the coating. Nitrogen protection avoids the oxidative degradation of the resin at high temperature, and ensures the modification stability.
[0015] Further, the use amount ratio of epoxy resin E-51, epichlorohydrin, anhydrous aluminum chloride and ethyl acetate in A1 is 400-500 g: 20-30 mL: 10-15 g: 5-8 mL.
[0016] Further, the use amount ratio of bisphenol A, sodium hydroxide and phthalic anhydride in A2 is 30-40 g: 5-8 g: 3-5 g.
[0017] Further, the use amount ratio of silane coupling agent KH-560, silane coupling agent KH-550 and polyvinyl butyral in A3 is 15-20 g: 5-8 g: 4-6 g.
[0018] Further, after adding bisphenol A, sodium hydroxide and phthalic anhydride in A2, the "water separation-viscosity real-time feedback" synergistic control process is adopted, the water generated in the reaction is continuously separated by a water separator to promote the forward reaction, and the viscosity is measured every hour, and when the viscosity reaches 5000-6000 mPa·s, phosphoric acid is immediately added for neutralization. This method can accurately control the chain extension of the molecular chain, control the molecular weight distribution width of the resin in the range of 1.2-1.5, make the mechanical properties of the coating uniform, reduce the risk of cracking and peeling, and lay a foundation for the stability of the subsequent coating.
[0019] Further, the modified nano zinc oxide is prepared according to the following steps:
[0020] B1, nano zinc oxide is added to an ethanol-water solution with a volume ratio of 3:1, ultrasonic dispersion for 30-40 min, then stearic acid and citric acid are added, and stirring is carried out at 500-600 r / min at 60-70℃ for 1-2 h, during which the pH is adjusted to 5-6 with dilute hydrochloric acid, and after the reaction is completed, filtration and drying are carried out to obtain surface esterification modified zinc oxide;
[0021] The initial agglomeration of nano zinc oxide is broken by ultrasonic dispersion, exposing more surface hydroxyl groups; under acidic conditions, the carboxyl groups of stearic acid and citric acid react with the surface hydroxyl groups of zinc oxide to introduce long-chain alkyl hydrophobic groups on the surface, significantly reducing the tendency of particle agglomeration and enhancing the wettability with the resin matrix, ensuring uniform dispersion in the coating and fully playing the role of corrosion protection and reinforcement;
[0022] B2, the above modified zinc oxide is added to deionized water to form a suspension, then aluminum nitrate, magnesium nitrate and zinc nitrate are added, and the pH is adjusted to 8-9 with ammonia water, and the reaction is carried out at 80-90℃ for 2-3 h, and during the reaction process, deionized water is added every 40 min to maintain the stability of the suspension concentration, and a composite oxide coating layer is formed, and after the reaction is completed, filtration is carried out, and drying is carried out at 100℃ for 3 h;
[0023] Under alkaline conditions, aluminum nitrate, magnesium nitrate and zinc nitrate are hydrolyzed to generate Al2O3, MgO and ZnO composite oxides, which uniformly coat the surface of zinc oxide to form a dense protective layer. The concentration of the suspension is maintained stable by adding deionized water to ensure the uniform thickness of the coating layer, enhance the chemical stability of the nanoparticles and block the direct contact path of the corrosion medium and the substrate.
[0024] B3, the dried powder is added to acetone, maleic anhydride grafted polyethylene wax and vinyl trimethoxysilane are added, and stirring is carried out at 500-600 r / min for 1-2 h at 50-60℃, during which condensation reflux is prevented to prevent the volatilization of acetone. After the reaction is completed, filtration is carried out, and vacuum drying is carried out at 60℃ for 2 h to obtain modified nano zinc oxide.
[0025] The maleic anhydride grafted polyethylene wax is combined with the surface hydroxyl groups of zinc oxide through polar groups, and the non-polar segments thereof are compatible with the resin matrix to strengthen the interface bonding. The alkoxyl groups of the vinyl trimethoxysilane are hydrolyzed to condense with the surface hydroxyl groups, and reactive vinyl groups are introduced to promote crosslinking reaction with the epoxy resin. Condensation reflux and vacuum drying ensure that the modifier is fully grafted and no solvent is left, and ultimately achieve uniform dispersion of nano zinc oxide in the coating, and synergistically play the roles of strengthening and corrosion prevention.
[0026] Further, the amount ratio of the nano zinc oxide, the ethanol aqueous solution, the stearic acid and the citric acid in B1 is 100-200 g: 250-350 mL: 10-15 g: 2-3 g.
[0027] Further, the amount ratio of the deionized water, the aluminum nitrate, the magnesium nitrate and the zinc nitrate in B2 is 200-250 mL: 5-8 g: 3-5 g: 2-4 g, and 1-2 mL of deionized water is added every 40 min.
[0028] Further, the amount ratio of the acetone, the maleic anhydride grafted polyethylene wax and the vinyl trimethoxysilane in B3 is 150-200 mL: 8-12 g: 3-5 g.
[0029] A preparation method of a solvent-free epoxy anticorrosive coating, specifically comprising the following steps:
[0030] S1, titanium dioxide, talc and barium sulfate are respectively ground through a ball mill and passed through a 900-mesh sieve; the modified nano zinc oxide, titanium dioxide, talc and barium sulfate are added to a dispersion kettle, and silane coupling agent KH-550 is added, high-speed stirring is started, and stirring and dispersion are carried out at 1400-1600 r / min for 30-40 min to obtain a uniform pigment and filler dispersion;
[0031] S2, the modified epoxy resin is added into the reaction kettle, the temperature is raised to 55 DEG C, butyl glycidyl ether, carboxyl-terminated butyl nitrile rubber are added in turn, 500-800r / min stirring mixing 15-20min, the resin base is obtained;
[0032] S3, the pigment filler dispersion is slowly added into the resin base, the stirring speed is controlled at 1200-1300r / min, mixing 25-35min, then the silicone defoaming agent is added, continue stirring 10-15min, ensure that the bubbles are fully eliminated;
[0033] S4, acrylic ester leveling agent, fumed silica are added into the above mixing system, stirring at 800-900r / min for 15-20min, the viscosity of the system is detected by rotary viscometer, and the viscosity is controlled at 8000-10000mPa・s;
[0034] S5, the system is cooled to 35 DEG C, the polyamide curing agent is added, 300-400r / min stirring 10-15min, ensure that the curing agent is uniformly mixed, the solvent-free epoxy anticorrosive coating is obtained.
[0035] Further, the grinding time of the ball mill in S1 is 2-3h, the grinding medium is zirconium oxide bead with a diameter of 1.5-2.0mm, and the material temperature is controlled at 35 DEG C during the grinding process
[0036] Further, in S4, when the viscosity is higher than 10000mPa・s, the amount of butyl glycidyl ether is increased by 5%, and when the viscosity is lower than 8000mPa・s, the amount of butyl glycidyl ether is reduced by 3%, so that the fluctuation range of the final viscosity is controlled within ±500mPa・s, the coating workability is stable, the sagging or coating difficulty is avoided, and the active diluent participates in the curing, so that the final performance of the coating is not affected.
[0037] The application provides a solvent-free epoxy anticorrosive coating and a preparation method.
[0038] 1. The synergistic effect of modified epoxy resin and modified nano zinc oxide realizes structure optimization. The molecular weight distribution of the modified epoxy resin is controlled to 1.2-1.5 through chain extension, and the flexibility and crosslinking density of the resin segment are improved through modification and modification of silane coupling agent and polyvinyl butyral. The modified nano zinc oxide is esterified, coated with a composite oxide and modified with silicone, which enhances the compatibility with the resin matrix, and can be uniformly dispersed and form a physical barrier. The combination of the two forms a dense and continuous network structure for the coating, which significantly improves the impact strength, adhesion and medium resistance of the coating, and effectively delays the penetration of corrosion medium.
[0039] 2. A fully solvent-free formulation is employed, with raw materials primarily consisting of non-volatile components such as modified epoxy resins and functional pigments and fillers. Process optimization during the preparation process reduces residual volatile substances, resulting in an extremely low VOC content in the final product, meeting environmental protection requirements. Furthermore, through dynamic adjustment of the dosage of butyl glycidyl ether and the synergistic toughening effect of carboxyl-terminated nitrile rubber, combined with a "real-time viscosity feedback" mechanism, the coating viscosity is stably controlled within a range of 8,000-10,000 mPa·s. This ensures leveling during application while preventing sagging, resolving the pain point of traditional solvent-free coatings: the difficulty in balancing environmental protection and workability.
[0040] 3. Pre-treating titanium dioxide, talc, barium sulfate, and modified nano-zinc oxide with the silane coupling agent KH-550, combined with a high-speed dispersion process, effectively breaks down pigment and filler agglomerates and achieves uniform dispersion. Simultaneously, the addition of fumed silica and an acrylate leveling agent synergistically inhibits pigment and filler settling and optimizes the coating surface. Combined with step-by-step mixing and viscosity control during the preparation process, the coating system remains stable during storage and application, preventing stratification and agglomeration and ensuring consistent coating performance.
[0041] 4. The polyamide curing agent and modified epoxy resin have a well-matched reactivity. Low-temperature, low-speed mixing ensures uniform curing agent dispersion and slow reaction. A silicone defoamer is used to eliminate bubbles during the mixing phase, and a leveling agent promotes a smooth coating surface. The entire curing process is free of defects such as bubbles and pinholes, resulting in a smooth, compact coating with a dense internal structure, significantly extending the coating's service life and protective life. DETAILED DESCRIPTION
[0042] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0043] Example 1: Preparation of solvent-free epoxy anti-corrosion coating. The specific preparation steps are as follows:
[0044] S1. Grind titanium dioxide, talc, and barium sulfate separately in a ball mill for 2 hours using zirconium oxide beads with a diameter of 1.5 mm as the grinding medium. Control the material temperature at 35°C during the grinding process and then pass through a 900-mesh sieve. Add 5 parts of nano zinc oxide, 10 parts of titanium dioxide, 8 parts of talc, and 5 parts of barium sulfate to a dispersion kettle, and then add 1 part of silane coupling agent KH-550. Start high-speed stirring at 1400 r / min and stir and disperse for 30 minutes to obtain a uniform pigment and filler dispersion.
[0045] S2, 40 parts of epoxy resin were added to the reaction kettle, heated to 55℃, 5 parts of butyl glycidyl ether, 3 parts of carboxyl-terminated butyl nitrile rubber were added in turn, 500 r / min stirring and mixing for 15 min, to get resin base;
[0046] S3, the pigment filler dispersion was slowly added to the resin base, the stirring speed was controlled at 1200 r / min, mixed for 25 min, then 0.5 parts of silicone defoaming agent was added, and stirring was continued for 10 min to ensure that the bubbles were fully eliminated;
[0047] S4, 0.5 parts of acrylic ester leveling agent and 1 part of fumed silica were added to the above mixing system, stirring at 800 r / min for 15 min, and the viscosity of the system was detected by rotary viscometer, and the viscosity was controlled at 8000 mPa・s;
[0048] S5, the system was cooled to 35℃, 15 parts of polyamide curing agent was added, 300 r / min stirring for 10 min, to ensure that the curing agent was mixed uniformly, to get solvent-free epoxy anticorrosive coating.
[0049] Example 2, preparation of solvent-free epoxy anticorrosive coating, the specific preparation steps are as follows:
[0050] S1, the titanium dioxide, talc and barium sulfate were ground by ball mill respectively, the grinding time was 3h, the grinding medium was zirconia bead with diameter of 2.0mm, the material temperature was controlled at 35℃ during the grinding process, and then passed through 900 mesh sieve; 10 parts of nano zinc oxide, 15 parts of titanium dioxide, 12 parts of talc, 8 parts of barium sulfate were added to the dispersion kettle, 2 parts of silane coupling agent KH-550 was added, high speed stirring was started, and stirring and dispersion was carried out at 1600 r / min for 40 min to get uniform pigment filler dispersion;
[0051] S2, 60 parts of epoxy resin were added to the reaction kettle, heated to 55℃, 10 parts of butyl glycidyl ether, 5 parts of carboxyl-terminated butyl nitrile rubber were added in turn, 800 r / min stirring and mixing for 20 min, to get resin base;
[0052] S3, the pigment filler dispersion was slowly added to the resin base, the stirring speed was controlled at 1300 r / min, mixed for 35 min, then 1 part of silicone defoaming agent was added, and stirring was continued for 15 min to ensure that the bubbles were fully eliminated;
[0053] S4, 1 part of acrylic ester leveling agent and 2 parts of fumed silica were added to the above mixing system, stirring at 900 r / min for 20 min, and the viscosity of the system was detected by rotary viscometer, and the viscosity was controlled at 10000 mPa・s;
[0054] S5, the system is cooled to 35℃, 25 parts of polyamide curing agent is added, 400 r / min stirring 15 min, ensure that the curing agent is mixed evenly, namely the solvent-free epoxy anticorrosive coating.
[0055] Example 3, preparation of solvent-free epoxy anticorrosive coating, the specific preparation steps are as follows:
[0056] S1, the titanium dioxide, talc, barium sulfate are respectively ground by ball mill, the grinding time is 2.5h, the grinding medium is zirconia bead with diameter of 1.7mm, the material temperature is controlled at 35℃ during the grinding process, and then the material is passed through a 900 mesh screen; 7 parts of nano zinc oxide, 12 parts of titanium dioxide, 10 parts of talc, 6 parts of barium sulfate are added into a dispersion kettle, 1.5 parts of silane coupling agent KH-550 is added, high speed stirring is started, and stirring and dispersion are carried out at 1500 r / min for 35 min to obtain a uniform pigment and filler dispersion;
[0057] S2, 50 parts of epoxy resin are added into a reaction kettle, heated to 55℃, 7 parts of butyl glycidyl ether and 4 parts of carboxyl-terminated butyl nitrile rubber are added in sequence, and stirring is carried out at 650 r / min for 18 min to obtain a resin base;
[0058] S3, the pigment and filler dispersion is slowly added into the resin base, the stirring speed is controlled at 1250 r / min, mixing is carried out for 30 min, 0.7 parts of silicone defoaming agent is added, and stirring is continued for 13 min to ensure that the bubbles are fully eliminated;
[0059] S4, 0.7 parts of acrylic ester leveling agent and 1.5 parts of fumed silica are added into the above mixing system, stirring is carried out at 850 r / min for 18 min, the viscosity of the system is detected by a rotary viscometer, and the viscosity is controlled at 9000 mPa・s;
[0060] S5, the system is cooled to 35℃, 20 parts of polyamide curing agent is added, 350 r / min stirring 12 min, ensure that the curing agent is mixed evenly, namely the solvent-free epoxy anticorrosive coating.
[0061] Example 4, preparation of modified epoxy resin, the specific preparation steps are as follows:
[0062] A1, 400g of epoxy resin E-51 is added into a reaction kettle, heated to 80℃, 20mL of epoxy chloropropane, 10g of anhydrous aluminum chloride and 5mL of ethyl acetate are slowly added under stirring at 400 r / min, and the reaction is kept for 2h. During the reaction, the epoxy value is measured every 30 min. When the epoxy value is stable at 0.35 eq / 100g, the reaction is stopped to obtain an epoxy ring-opening prepolymer;
[0063] A2, 30 g of bisphenol A, 5 g of sodium hydroxide and 3 g of phthalic anhydride were added to the above prepolymer, heated to 110°C, reacted for 3 h, and water generated during the reaction was separated by a water trap. The viscosity was measured every hour, and when the viscosity reached 5000 mPa·s, 2 mL of phosphoric acid was added to neutralize the remaining alkalinity to obtain a chain-extended modified epoxy intermediate;
[0064] A3, the above intermediate was cooled to 70°C, 15 g of silane coupling agent KH-560, 5 g of silane coupling agent KH-550 and 4 g of polyvinyl butyral were added, and stirred at 500 r / min for 1 h. Nitrogen was introduced during the reaction, and the reaction was cooled to room temperature after the reaction was completed to obtain a modified epoxy resin.
[0065] Example 5, a modified epoxy resin was prepared, and the specific preparation steps were as follows:
[0066] A1, 500 g of epoxy resin E-51 was added to a reaction kettle, heated to 90°C, and 30 mL of epoxy chloropropane, 15 g of anhydrous aluminum chloride and 8 mL of ethyl acetate were slowly added under stirring at 500 r / min. After addition, the reaction was maintained for 3 h, and the epoxy value was measured every 30 min during the reaction. When the epoxy value was stable at 0.4 eq / 100 g, the reaction was stopped to obtain an epoxy ring-opening prepolymer;
[0067] A2, 40 g of bisphenol A, 8 g of sodium hydroxide and 5 g of phthalic anhydride were added to the above prepolymer, heated to 120°C, reacted for 4 h, and water generated during the reaction was separated by a water trap. The viscosity was measured every hour, and when the viscosity reached 6000 mPa·s, 3 mL of phosphoric acid was added to neutralize the remaining alkalinity to obtain a chain-extended modified epoxy intermediate;
[0068] A3, the above intermediate was cooled to 80°C, 20 g of silane coupling agent KH-560, 8 g of silane coupling agent KH-550 and 6 g of polyvinyl butyral were added, and stirred at 600 r / min for 2 h. Nitrogen was introduced during the reaction, and the reaction was cooled to room temperature after the reaction was completed to obtain a modified epoxy resin.
[0069] Example 6, a modified nano zinc oxide was prepared, and the specific preparation steps were as follows:
[0070] B1, 100 g of nano zinc oxide was added to 250 mL of an ethanol water solution with a volume ratio of 3:1, ultrasonically dispersed for 30 min, and then 10 g of stearic acid and 2 g of citric acid were added. The reaction was stirred at 500 r / min for 1 h at 60°C, and the pH was adjusted to 5 with dilute hydrochloric acid during the reaction. After the reaction, the product was filtered and dried to obtain surface esterification modified zinc oxide;
[0071] B2, the modified zinc oxide is added into 200 mL of deionized water to form a suspension, 5 g of aluminum nitrate, 3 g of magnesium nitrate and 2 g of zinc nitrate are added, the pH is adjusted to 8 with ammonia water, and the reaction is carried out at 80°C for 2 h, during which 1 mL of deionized water is added every 40 min to maintain the concentration of the suspension stable, a composite oxide coating layer is generated, and after the reaction is completed, the mixture is filtered and dried at 100°C for 3 h;
[0072] B3, the dried powder is added into 150 mL of acetone, 8 g of maleic anhydride grafted polyethylene wax and 3 g of vinyl trimethoxysilane are added, the mixture is stirred at 500 r / min at 50°C for 1 h, during which condensation reflux is carried out to prevent the volatilization of acetone, after the reaction is completed, the mixture is filtered and vacuum dried at 60°C for 2 h to obtain the modified nano zinc oxide.
[0073] Example 7, preparation of modified nano zinc oxide, the specific preparation steps are as follows:
[0074] B1, 120 g of nano zinc oxide is added into 350 mL of an ethanol water solution with a volume ratio of 3:1, and ultrasonic dispersion is carried out for 40 min, 15 g of stearic acid and 3 g of citric acid are added, the mixture is stirred at 600 r / min at 70°C for 2 h, during which the pH is adjusted to 6 with dilute hydrochloric acid, and after the reaction is completed, the mixture is filtered and dried to obtain surface esterification modified zinc oxide;
[0075] B2, the modified zinc oxide is added into 250 mL of deionized water to form a suspension, 8 g of aluminum nitrate, 5 g of magnesium nitrate and 4 g of zinc nitrate are added, the pH is adjusted to 9 with ammonia water, and the reaction is carried out at 90°C for 3 h, during which 2 mL of deionized water is added every 40 min to maintain the concentration of the suspension stable, a composite oxide coating layer is generated, and after the reaction is completed, the mixture is filtered and dried at 100°C for 3 h;
[0076] B3, the dried powder is added into 200 mL of acetone, 12 g of maleic anhydride grafted polyethylene wax and 5 g of vinyl trimethoxysilane are added, the mixture is stirred at 600 r / min at 60°C for 2 h, during which condensation reflux is carried out to prevent the volatilization of acetone, after the reaction is completed, the mixture is filtered and vacuum dried at 60°C for 2 h to obtain the modified nano zinc oxide.
[0077] Comparative Example 1, preparation of a solvent-free epoxy anticorrosive coating, the specific preparation steps are as follows:
[0078] The remaining steps are unchanged, only the epoxy resin of Example 3 is replaced with the modified epoxy resin prepared in Example 4 to prepare a solvent-free epoxy anticorrosive coating.
[0079] Comparative Example 2, preparation of a solvent-free epoxy anticorrosive coating, the specific preparation steps are as follows:
[0080] The remaining steps are unchanged, only the nano zinc oxide of Example 3 is replaced with the modified nano zinc oxide prepared in Example 7 to prepare a solvent-free epoxy anticorrosive coating.
[0081] Comparative Example 3, a solvent-free epoxy anticorrosive coating was prepared, and the specific preparation steps were as follows:
[0082] The remaining steps are unchanged, only the epoxy resin and nano zinc oxide of Example 3 are replaced with the modified epoxy resin prepared in Example 4 and the modified nano zinc oxide prepared in Example 7 to prepare a solvent-free epoxy anticorrosive coating.
[0083] Performance test
[0084] Test item Test standard Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Adhesion (crosshatch method) GB / T 9286-2021 Level 3 Level 3 Level 2 Level 2 Level 2 Level 1 Impact resistance (kg·cm) GB / T 1732-2020 30 35 40 45 50 60 Salt spray resistance (h) GB / T 1771-2007 500 550 600 750 800 1000 Pencil hardness GB / T 6739-2022 HB HB B B H 2H Viscosity stability (30d change rate, %) GB / T 6753.3-1986 8.5 7.2 6.8 6.5 5.2 3.8 VOC content (g / L) GB / T 23985-2009 <10 <10 <10 <10 <10 <10 Drying time (surface dry, h) GB / T 1728-2020 4 4 3.5 3.5 3 3
[0085] According to the performance test results, the solvent-free epoxy anticorrosive coating of the present application performs excellently in environmental protection, and the VOC content of all examples and comparative examples is <10 g / L, meeting the green environmental protection requirements; the drying time is 3-4 h, and the construction efficiency is relatively high. In terms of mechanical properties, the adhesion is mostly 2-3 levels, the impact resistance is 30-60 kg·cm, the pencil hardness covers HB to 2H, and through the synergistic effect of modified nano zinc oxide and modified epoxy resin in Comparative Example 3, the impact resistance is improved to 60 kg·cm, the pencil hardness reaches 2H, and the mechanical properties are significantly enhanced. In terms of corrosion resistance, the salt spray resistance is 500-1000 h, among which the salt spray resistance of Comparative Example 3 using double modified raw materials is optimal, reaching 1000 h. In addition, the coating viscosity stability is good, the 30d change rate is 3.8%-8.5%, the viscosity stability of Comparative Example 3 is the best, the change rate is only 3.8%, and the overall comprehensive performance is obviously optimized with the application of modified raw materials.
[0086] The above is only an example and description of the present application, and those skilled in the art can make various modifications or supplements to the described specific examples or use similar ways to replace, as long as they do not deviate from the invention or exceed the scope defined by the present claims, which should belong to the protection scope of the present application.
Claims
1. A solvent-free epoxy anticorrosive coating, characterized by: The invention comprises the following raw materials in parts by weight: 40-60 parts of modified epoxy resin, 5-10 parts of modified nano zinc oxide, 15-25 parts of polyamide curing agent, 5-10 parts of butyl glycidyl ether, 10-15 parts of titanium dioxide, 8-12 parts of talc, 5-8 parts of barium sulfate, 0.5-1 part of silicone defoaming agent, 0.5-1 part of acrylic leveling agent, 1-2 parts of silane coupling agent KH-550, 3-5 parts of carboxyl-terminated nitrile rubber, and 1-2 parts of fumed silica.
2. The solvent-free epoxy anticorrosive coating according to claim 1, characterized in that: The modified epoxy resin is specifically prepared in the following steps: A1. Add epoxy resin E-51 to a reactor, raise the temperature to 80-90°C, and slowly add epichlorohydrin, anhydrous aluminum chloride, and ethyl acetate under stirring at 400-500 r / min. After the addition is complete, keep the reaction warm for 2-3 hours. During this period, measure the epoxy value every 30 minutes. Stop the reaction when the epoxy value stabilizes at 0.35-0.4 eq / 100g to obtain an epoxy ring-opening prepolymer. A2. Add bisphenol A, sodium hydroxide, and phthalic anhydride to the above prepolymer, raise the temperature to 110-120° C., and react for 3-4 hours. During this time, separate the generated water through a water separator, take samples every hour to measure the viscosity, and when the viscosity reaches 5000-6000 mPa·s, add phosphoric acid to neutralize the residual alkalinity to obtain a chain-extended modified epoxy intermediate; A3. Cool the intermediate to 70-80° C., add silane coupling agent KH-560, silane coupling agent KH-550 and polyvinyl butyral, and stir at 500-600 r / min for 1-2 h. During this period, introduce nitrogen protection. After the reaction is completed, cool to room temperature to obtain a modified epoxy resin.
3. The solvent-free epoxy anticorrosive coating according to claim 2, characterized in that: The usage ratio of epoxy resin E-51, epichlorohydrin, anhydrous aluminum chloride, and ethyl acetate in A1 is 400-500 g: 20-30 mL: 10-15 g: 5-8 mL; The usage ratio of bisphenol A, sodium hydroxide and phthalic anhydride in A2 is 30-40g:5-8g:3-5g; The usage ratio of silane coupling agent KH-560, silane coupling agent KH-550 and polyvinyl butyral in A3 is 15-20g: 5-8g: 4-6g.
4. The solvent-free epoxy anticorrosive coating according to claim 2, characterized in that: After adding bisphenol A, sodium hydroxide, and phthalic anhydride to A2, a "water separation-viscosity real-time feedback" collaborative control process is adopted. The water generated by the reaction is continuously separated by a water separator to promote the forward reaction. The viscosity is measured hourly. When the viscosity reaches 5000-6000 mPa·s, phosphoric acid is immediately added for neutralization. This method can accurately control the degree of molecular chain extension, keeping the resin molecular weight distribution width within the range of 1.2-1.
5.
5. The solvent-free epoxy anti-corrosion coating according to claim 1, characterized in that: The modified nano zinc oxide is specifically prepared in the following steps: B1. Add nano zinc oxide to an ethanol-water solution with a volume ratio of 3:1, ultrasonically disperse for 30-40 minutes, then add stearic acid and citric acid, and stir at 500-600 r / min at 60-70°C for 1-2 hours. During this period, adjust the pH to 5-6 with dilute hydrochloric acid. After the reaction is completed, filter and dry to obtain surface esterified modified zinc oxide; B2. Add the modified zinc oxide to deionized water and stir to form a suspension. Then add aluminum nitrate, magnesium nitrate and zinc nitrate. Adjust the pH to 8-9 with aqueous ammonia. React at 80-90°C for 2-3 hours. During the reaction, add deionized water every 40 minutes to maintain a stable concentration of the suspension to form a composite oxide coating. After the reaction, filter and dry at 100°C for 3 hours. B3. Add the dried powder to acetone, then add maleic anhydride grafted polyethylene wax and vinyl trimethoxysilane, and stir at 50-60°C and 500-600 r / min for 1-2 hours. During this period, condense and reflux to prevent acetone from volatilizing. After the reaction is completed, filter and vacuum dry at 60°C for 2 hours to obtain modified nano zinc oxide.
6. The solvent-free epoxy anti-corrosion coating according to claim 5, characterized in that: The dosage ratio of nano zinc oxide, ethanol aqueous solution, stearic acid and citric acid in B1 is 100-200g:250-350mL:10-15g:2-3g; The dosage ratio of deionized water, aluminum nitrate, magnesium nitrate, and zinc nitrate in B2 is 200-250 mL: 5-8 g: 3-5 g: 2-4 g; 1-2 mL of deionized water is added every 40 minutes; The usage ratio of acetone, maleic anhydride grafted polyethylene wax, and vinyltrimethoxysilane in B3 is 150-200 mL: 8-12 g: 3-5 g.
7. A method for preparing a solvent-free epoxy anticorrosive coating, characterized in that: The specific steps include: S1. Grind titanium dioxide, talc, and barium sulfate separately using a ball mill and pass through a 900-mesh sieve; add modified nano zinc oxide, titanium dioxide, talc, and barium sulfate into a dispersion kettle, then add silane coupling agent KH-550, start high-speed stirring at 1400-1600 r / min and stir and disperse for 30-40 minutes to obtain a uniform pigment and filler dispersion; S2. Add the modified epoxy resin into the reactor, heat it to 55° C., add butyl glycidyl ether and carboxyl-terminated nitrile rubber in sequence, and stir and mix at 500-800 r / min for 15-20 min to obtain a resin base material; S3. Slowly add the pigment and filler dispersion to the resin base, control the stirring speed to 1200-1300 r / min, mix for 25-35 minutes, then add the silicone defoamer and continue stirring for 10-15 minutes to ensure that the bubbles are fully eliminated; S4. Add acrylate leveling agent and fumed silica to the above mixed system, stir at 800-900 r / min for 15-20 min, and use a rotational viscometer to detect the viscosity of the system and control the viscosity at 8000-10000 mPa·s; S5. Cool the system to 35°C, add polyamide curing agent, and stir at 300-400 r / min for 10-15 minutes to ensure that the curing agent is evenly mixed to obtain a solvent-free epoxy anti-corrosion coating.
8. The solvent-free epoxy anticorrosive coating according to claim 7, characterized in that: The ball mill grinding time in S1 is 2-3 hours, the grinding medium is zirconia beads with a diameter of 1.5-2.0 mm, and the material temperature is controlled at 35° C. during the grinding process.
9. The solvent-free epoxy anticorrosive coating according to claim 7, characterized in that: In the above-mentioned S4, when the viscosity is higher than 10000 mPa·s, the amount of butyl glycidyl ether is increased by 5%, and when it is lower than 8000 mPa·s, the amount of butyl glycidyl ether is reduced by 3%, ensuring that the final viscosity fluctuation range is controlled within ±500 mPa·s.
Citation Information
Patent Citations
Low temperature cured solvent-free epoxy anticorrosion paint and its preparation method
CN102382552A
Solvent-free nanometer epoxy anticorrosive paint and preparation method thereof
CN103232786A
Anticorrosive coating and preparation method thereof
CN113337184A
Curable slurry of epoxy resin-polyvinyl butyral composite material and preparation method thereof
CN119798923A
Cited By
External 3PE and internal epoxy resin anti-corrosion pipeline and production process thereof
CN121017066A